Cranial Base Reconstruction and Secondary Frontal Advancement for Meningoencephalocele Following LeFort III Osteotomy in a Patient with Crouzon Syndrome: Case Report - Jeon, Sungmi; Kim, Yumin; Phi, Ji Hoon; Chung, Jee Hyuk (Archives of Plastic Surgery, 2023)
Patients with Crouzon syndrome have increased risks of cerebrospinal fluid rhinorrhea and meningoencephalocele after LeFort III osteotomy. We report a rare case of meningoencephalocele following LeFort III midface advancement in a patient with Crouzon syndrome. Over 10 years since it was incidentally found during transnasal endoscopic orbital decompression, the untreated meningoencephalocele eventually led to intermittent clear nasal discharge, frontal headache, and seizure. Computed tomography and magnetic resonance imaging demonstrated meningoencephalocele in the left frontal-ethmoid-maxillary sinus through a focal defect of the anterior cranial base. Through bifrontal craniotomy, the meningoencephalocele was removed and the anterior cranial base was reconstructed with a pericranial flap and split calvarial bone graft. Secondary frontal advancement was concurrently performed to relieve suspicious increased intracranial pressure, limit visual deterioration, and improve the forehead shape. Surgeons should be aware that patients with Crouzon syndrome have the potential for an unrecognized dural injury during LeFort III osteotomy due to anatomical differences such as inferior displacement and thinning of the anterior cranial base.
Keywords: LeFort osteotomy; Crouzon syndrome; meningoencephalocele; magnetic resonance imaging; computed tomography